Wake‐promoting actions of noradrenergic α1‐ and β‐receptors within the lateral hypothalamic area. Issue 6 (18th December 2012) - Schmeichel, Brooke E.; Berridge, Craig W.
Abstract: Central norepinephrine exerts potent wake‐promoting effects, in part through the actions of noradrenergic α1 ‐ and β‐receptors located in the medial septal and medial preoptic areas. The lateral hypothalamic area (LHA), including the lateral hypothalamus, perifornical area and adjacent dorsomedial hypothalamus, is implicated in the regulation of arousal and receives a substantial noradrenergic innervation. To date the functional significance of this innervation is unknown. The current studies examined the degree to which noradrenergic α1 ‐ and β‐receptor stimulation within the rat LHA modulates arousal. Specifically, these studies examined the wake‐promoting effects of intra‐tissue infusions (250 nL) of the α1 ‐receptor agonist phenylephrine (10, 20 and 40 nmol) and the β‐receptor agonist isoproterenol (3, 10 and 30 nmol) in rats. Results show that stimulation of LHA α1 ‐receptors elicits robust and dose‐dependent increases in waking. In contrast, β‐receptor stimulation within the LHA had relatively modest arousal‐promoting actions. Nonetheless, combined α1 ‐ and β‐receptor stimulation elicited additive wake‐promoting effects. Arousal‐promoting hypocretin/orexin (HCRT)‐synthesising neurons are located within the LHA. Therefore, additional immunohistochemical studies examined whether α1 ‐receptor‐dependent waking is associated with an activation of HCRT neurons as measured byFos, the protein product of the immediate–early gene c‐fos . Analyses indicate that although intra‐LHA α1 ‐receptor agonist infusion elicited a robust increase inFos immunoreactivity (ir) in this region, this treatment did not activate HCRT neurons as measured by Fos‐ir. Collectively, these observations indicate that noradrenergic α1 ‐receptors within the LHA promote arousal via actions that are independent of HCRT neuronal activation. Abstract : Central norepinephrine exerts potent wake‐promoting effects, in part, through the actions of noradrenergic α1 ‐ and β‐receptors located in the medial septal and medial preoptic areas. The lateral hypothalamic area (LHA), including the lateral hypothalamus, perifornical area and adjacent dorsomedial hypothalamus, is implicated in the regulation of arousal and receives a moderate noradrenergic innervation. The current studies demonstrate that noradrenergic a1‐ and B‐receptors within the LHA promote waking in the absence of an activation of hypocretin neurons as measured by Fos immunoreactivity.